2001
DOI: 10.1155/edr.2001.187
|View full text |Cite
|
Sign up to set email alerts
|

Human C‐peptide Dose Dependently Prevents Early Neuropathy in the BB/Wor‐rat

Abstract: In order to explore the neuroprotective and crossspecies activities of.C-peptide on type 1 diabetic neuropathy, spontaneously diabetic BB/W-rats were given increasing doses of human recombinant Cpeptide (hrC-peptide). Diabetic rats received 10, 100, 500, or 1000 μg of hrC-peptide/kg body weight/ day from onset of diabetes. After 2 months of hrC-peptide administration, 100 μg and greater doses completely prevented the nerve conduction defect, which was associated with a significant but incomplete prevention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 20 publications
4
48
0
Order By: Relevance
“…These changes are likely to reflect early circulatory and metabolic disturbances of the peripheral nerves rather than structural changes, and the sensory defects indicate the presence of subclinical neuropathy. The present study shows for the first time in patients that C-peptide in replacement doses has the capacity to improve the early neurological changes that accompany type 1 diabetes, as previously demonstrated in rat models of type 1 diabetes (12,18,22). The NCV in the sural nerve had increased significantly after only 6 weeks of C-peptide treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These changes are likely to reflect early circulatory and metabolic disturbances of the peripheral nerves rather than structural changes, and the sensory defects indicate the presence of subclinical neuropathy. The present study shows for the first time in patients that C-peptide in replacement doses has the capacity to improve the early neurological changes that accompany type 1 diabetes, as previously demonstrated in rat models of type 1 diabetes (12,18,22). The NCV in the sural nerve had increased significantly after only 6 weeks of C-peptide treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Because full saturation of C-peptide binding sites already occurs at the ambient C-peptide concentration in healthy subjects, further physiological effects cannot be expected when the concentration is increased above the saturation level. Dose-dependency for C-peptide effects have been demonstrated in vivo in animal models of diabetes and in type 1 diabetic patients (27,29). It is noteworthy that the patients included in the present study all had C-peptide plasma concentrations Ͻ0.2 nmol/l at baseline.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, raising the concentration above this level would not be expected to elicit any further physiological effects. In fact, dose dependency for C-peptide in the concentration range of 0 -1.0 nmol/l has been demonstrated in vitro as well as in vivo in rats and humans (27)(28)(29), but with concentrations above the physiological level the responses have not been greater. The findings for the higher dose group thus provide support for the view that C-peptide should be given as a physiological replacement.…”
Section: Ekberg and Associatesmentioning
confidence: 99%
“…Experimental studies in type 1 diabetes showed that C-peptide specifically bound to cell surfaces, acting via a Gprotein-related receptor; it also led to autophosphorylation of the insulin receptor in the presence of insulin [20] . Moreover, C-peptide stimulated p38 MAP-kinase and PI-3 kinase activities, and diminished the activation of JNK phosphorylation with subsequent effects on Na + /K + -ATPase activity and nitric oxide (NO) [21,22] . C-peptide also ameliorated the altered expression of insulin-like growth factor-1, nerve growth factor and neurotrophin-3 and their respective receptors, which corrected neurofilament (NF) and tubulin mRNA, and protein expression, as well as normalized the aberrant phosphorylation of NFs [23] .…”
Section: Discussionmentioning
confidence: 99%